Properties of breaking irregular waves over slopes. (15th November 2020) - Aggarwal, Ankit; Alagan Chella, Mayilvahanan; Bihs, Hans; Myrhaug, Dag
Abstract: The present study numerically investigates the breaking and spectral characteristics and geometric properties of breaking irregular waves over slopes for different incident waves. The growth of wave non-linearity and wave energy redistribution during shoaling and breaking process are observed to be major factors in determining the free surface elevation skewness and spectral bandwidth. In general, the variation of the breaker indices with the surf similarity parameter is found to be mainly governed by the type of wave breakers. The wave breaker type further depends on the seabed slope, incident wave parameters and water depth at the location of wave breaking. The study further explores the geometric properties for both spilling and plunging irregular wave breakers. The wave deformation due to wave-seabed interaction plays a major role in affecting the breaker shapes. Every individual breaking wave in the irregular wave train possesses different wave profiles and breaker characteristics. In order to study these parameters in a probabilistic way, the statistics of the breaker characteristics and the breaker shape parameters are investigated. The lognormal distribution is noticed to be the most suitable fit for the wave crest steepness and asymmetry factors. This study is performed using the open-source computational fluid dynamics (CFD) based numerical model. The numerical model is validated for a submerged bar under breaking irregular waves and the numerical results are compared with experimental data. The transformations of the free surface elevation due to wave shoaling, wave breaking and wave decomposition are explored. Highlights: Numerical modelling of breaking irregular waves. Validation of numerical model with experimental data. Hydrodynamic and spectral characteristics of breaking irregular waves. Wave profile geometric properties of breaking irregular waves. Statistics of hydrodynamic and wave profile geometric properties.